Helping editors, peer reviewers and authors improve the clarity, completeness and transparency of reporting health research. - Moher, D; Simera, I; Schulz, K; Hoey, J; Altman, D (BioMed Central, 2008)
Inadequate reporting is problematic for several reasons. If authors do not provide sufficient details concerning the conduct of their study, readers are left with an incomplete picture of what was done. As such, they are not able to judge the merits of the results and interpret them. The EQUATOR Network is a new initiative aimed at improving the clarity and transparency of reporting health research.